2009
DOI: 10.1097/bcr.0b013e318198a2e8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Study of SilvaSorb® Gel in Comparison to Silvadene® Silver Sulfadiazine Cream in the Management of Partial-Thickness Burns

Abstract: This prospective, randomized study assessed the clinical, microbiological, and patient comfort characteristics of two silver-based topical agents in the management of partial-thickness burn wounds. Pediatric patients were randomly assigned to treatment with either SilvaSorb Gel (Medline Industries, Munedelein, IL) or Silvadene silver sulfadiazine cream (King Pharmaceuticals, Bristol, TN) for up to 21 days or to the point of full reepithelialization of the wound. Inclusion criteria were patients ranging in age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 7 publications
0
22
0
1
Order By: Relevance
“…In a prospective, randomised study, Glat et al (21) assessed the clinical and microbiological characteristics of two silver‐based topical agents in the management of paediatric partial‐thickness burns. Twenty‐four patients ranging in age from 2 months to 18 years with total body surface area (TBSA) burns ranging from 1% up to 40% were enrolled and completed the study.…”
Section: How the Dressing Technology Can Assist In Managing Painmentioning
confidence: 99%
“…In a prospective, randomised study, Glat et al (21) assessed the clinical and microbiological characteristics of two silver‐based topical agents in the management of paediatric partial‐thickness burns. Twenty‐four patients ranging in age from 2 months to 18 years with total body surface area (TBSA) burns ranging from 1% up to 40% were enrolled and completed the study.…”
Section: How the Dressing Technology Can Assist In Managing Painmentioning
confidence: 99%
“…Although SSD cream has been a mainstay of burn care since 1967 [1] and has excellent antibacterial properties, it has been suggested that it does not result in as fast wound healing as other agents. Some authors have suggested that SSD is a more painful treatment than other enzymatic or topical dressings [10].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a number of adverse outcomes are observed when using silver-based dressings such as delayed or incomplete re-epithelialization, scar discoloration, and hypersensitivity (Hussain and Ferguson, 2006 ; Wang et al, 2009a ). For this reason, novel delivery systems for silver-based therapeutics have been developed including silver-loaded hydrogels (Boonkaew et al, 2014 ), which have found success in clinical applications (Glat et al, 2009 ). Even though there was no difference in infection rate between the silver-loaded hydrogel and SSD, there was a decrease in patient pain during dressing changes (Glat et al, 2009 ).…”
Section: Inflammationmentioning
confidence: 99%
“…For this reason, novel delivery systems for silver-based therapeutics have been developed including silver-loaded hydrogels (Boonkaew et al, 2014 ), which have found success in clinical applications (Glat et al, 2009 ). Even though there was no difference in infection rate between the silver-loaded hydrogel and SSD, there was a decrease in patient pain during dressing changes (Glat et al, 2009 ). In one report, a hydrofiber dressing coated with ionic silver reduced the incidence of burn wound infections, reduced pain, and accelerated wound closure when compared to SSD.…”
Section: Inflammationmentioning
confidence: 99%